2022
DOI: 10.53378/352938
|View full text |Cite
|
Sign up to set email alerts
|

Using Reader Response Strategy and Affective Learning Domain in Teaching Literature to Enhance Critical Thinking

Abstract: Reading comprehension has been a perennial problem for Filipino students which was reflected in the Program for International Student Assessment (PISA) and in San Bartolome Integrated High School’s Secondary Reading Inventory (SRI) which showed that 281 out of 920 students were at the frustration level of reading. The strategy used by the teacher and reading interest of the students affect students’ learning. This experimental study aimed to find out the effect of Reader Response Strategy in teaching literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…The high level of affective domain affecting the students' reading comprehension found a support on the findings of Zolgar et al (2018) which showed that positive or negative attitude toward reading activities has a significant influence on the amount of reading for pleasure and a child's reading achievement. The important role in education of the affective domain has been underpinned by Suarez & Diva (2022). In fact, people learn quickly when they feel safe, relaxed, included, and interested.…”
Section: Mean Level Of Reading Comprehension Learning Domains In Term...mentioning
confidence: 99%
“…The high level of affective domain affecting the students' reading comprehension found a support on the findings of Zolgar et al (2018) which showed that positive or negative attitude toward reading activities has a significant influence on the amount of reading for pleasure and a child's reading achievement. The important role in education of the affective domain has been underpinned by Suarez & Diva (2022). In fact, people learn quickly when they feel safe, relaxed, included, and interested.…”
Section: Mean Level Of Reading Comprehension Learning Domains In Term...mentioning
confidence: 99%